Bisimidazolium Salt Glycosyltransferase Inhibitors Suppress Hepatocellular Carcinoma Progression In Vitro and In Vivo - Xue Luan; Ming Sun; Xue Zhao; Jingyi Wang; Ye Han; Yin Gao (MDPI AG, 2022)
Hepatocellular carcinoma is a leading cause of cancer death, and the disease progression has been related to glycophenotype modifications. Previously synthesized bisimidazolium salts (C20 and C22) have been shown to selectively inhibit the activity of glycosyltransferases in cultured cancer cell homogenates. The current study investigated the anticancer effects of C20/C22 and the possible pathways through which these effects are achieved. The therapeutic value of C20/C22 in terms of inhibiting cancer cell proliferation, metastasis, and angiogenesis, as well as inducing apoptosis, were examined with hepatic cancer cell line HepG2 and a xenograft mouse model. C20/C22 treatment downregulated the synthesis of SLex and Ley sugar epitopes and suppressed selectin-mediated cancer cell metastasis. C20/C22 inhibited HepG2 proliferation, induced cell-cycle arrest, increased intracellular ROS level, led to ER stress, and eventually induced apoptosis through the intrinsic pathway. Furthermore, C20/C22 upregulated the expressions of death receptors DR4 and DR5, substantially increasing the sensitivity of HepG2 to TRAIL-triggered apoptosis. In vivo, C20/C22 effectively inhibited tumor growth and angiogenesis in the xenograft mouse model without adverse effects on major organs. In summary, C20 and C22 are new promising anti-hepatic cancer agents with multiple mechanisms in controlling cancer cell growth, metastasis, and apoptosis, and they merit further development into anticancer drugs.